Importance of Seed Anthracnose on Beans - Alemu, Melkam Anteneh (International Journal For Research In Agricultural And Food Science, 2019)
Disease infected seed can have reduced storability, decreased germination, loss of seed weight and reduced meal and oil quality. Optimum storage conditions to limit fungal growth includes: Seed free from fungi or other pests, Clean seed without organic or other waste material, Less than 12% moisture, and Cool uniform storage temperature. Management options to minimize diseases on seed: Start with clean seed (pathogen free) and use resistant varieties when available. Fungicide options Seed treatments can help reduced seed to seedling disease transfer. Foliar fungicides can help reduced the risk to pod and seed infection by some fungi. Tillage and crop rotation – bury the inoculum from disease-infested residue and further reduced the inoculum by planting a non-host the next season. When at threshold levels, control pests, such as bean leaf beetle, and other insects that injure the pod, opening the door to fungal infection. Infected seed also can introduce new races of the pathogen into different geographic regions. Anthracnose can move into new fields with infected seed, which give rise to diseased seedlings that act as a source of inoculums of the anthracnose fungus that is spread to adjacent plants by splashing rain. Sowing infected seed also results in poorer emergence and reduced seedling vigor. Seed producers need to maintain very high standards of disease control in order to maximize yield and provide bean producers with high quality, disease-free seed. Growers should have seed samples tested to ensure they are not infected. The use of disease-free seed is a critical component of any strategy to prevent losses caused by this disease.